2000
DOI: 10.1099/00221287-146-4-829
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Rhizobium leguminosarum siderophore-uptake gene fhuA: differential expression in free-living bacteria and nitrogen-fixing bacteroids and distribution of an fhuA pseudogene in different strains The GenBank/EMBL/DDBJ accession number for the sequence determined in this work is AJ238208.

Abstract: A mutation was isolated in the Rhizobium leguminosarum gene fhuA, which appears to specify the outer-membrane receptor for the siderophore vicibactin. The mutant was defective in iron uptake and accumulated the siderophore vicibactin in the extracellular medium. Expression of fhuA was regulated by Fe 3M , transcription being higher in iron-depleted cells. Transcription of fhuA was independent of a functional copy of rpoI, a neighbouring gene that specifies a putative ECF σ factor of RNA polymerase and which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 39 publications
1
40
0
1
Order By: Relevance
“…Several rhizobial species have been reported to produce siderophores under culture conditions [10,11] , but there is no evidence that these siderophores are made in planta. There are also evidences that mature N 2 -fixing bacteroids of R. leguminosarum do not transcribe the vicibactin uptake receptor gene at detectable levels [49] . It is possible that FegA also does not have anything to do with iron uptake in planta [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Several rhizobial species have been reported to produce siderophores under culture conditions [10,11] , but there is no evidence that these siderophores are made in planta. There are also evidences that mature N 2 -fixing bacteroids of R. leguminosarum do not transcribe the vicibactin uptake receptor gene at detectable levels [49] . It is possible that FegA also does not have anything to do with iron uptake in planta [2] .…”
Section: Discussionmentioning
confidence: 99%
“…R. leguminosarum contains a receptor for vicibactin (FhuA) whose expression is induced in free-living cultures under low Fe conditions (Yeoman et al 2000). Interestingly, fhuA expression is also induced in the meristematic zone of pea nodules, but not in mature bacteroids.…”
Section: Transporters For Metal Uptake Through the Outer Membranementioning
confidence: 98%
“…Interestingly, fhuA expression is also induced in the meristematic zone of pea nodules, but not in mature bacteroids. Mutations in fhuA, however, do not show signifi cant effects on symbiotic performance (Yeoman et al 2000). The TBDT for Fe-rhizobactin complex is encoded by Sinorhizobium meliloti rhtA.…”
Section: Transporters For Metal Uptake Through the Outer Membranementioning
confidence: 99%
“…In R. leguminosarum field-isolated J251, we had shown that the uptake of VB is mediated by the Fhu transport proteins, the outer-membrane receptor being FhuA, the periplasmic binding protein FhuD, the inner-membrane transporter FhuB and the ATPase FhuC (Stevens et al, 1999;Yeoman et al, 2000). Analysis of the genome of the sequenced R. leguminosarum field isolate 3841 showed that it has two fhuA genes, with 'fhuA1' being on the symbiotic plasmid, pRL10JI,~145 kb from the nod genes (http:// www.sanger.ac.uk/Projects/R_leguminosarum/) and the other copy, 'fhuA2' being in the fhuA2F-rpoI-vbs gene cluster on a different native plasmid, pRL12JI.…”
Section: Different Arrangements Of Fhua Genes In Different Field Isolmentioning
confidence: 99%
“…Mutations in rirA cause deregulated expression of several genes whose transcription is normally repressed in cells grown in Fe-replete medium. These include the vbs and fhu genes, which are involved, respectively, in the synthesis and uptake of the siderophore vicibactin (VB) (Carter et al, 2002;Stevens et al, 1999;Yeoman et al, 2000); hmuPSTUV, which specifies a haem ABC transporter ; tonB ; and rpoI, which encodes an ECF s factor that specifically recognizes promoters of the vbsADL and vbsGSO VB biosynthetic genes (Yeoman et al, 1999(Yeoman et al, , 2003. Transcription of rirA itself is enhanced in Fe-replete conditions and is auto-regulated (Todd et al, 2002).…”
Section: Introductionmentioning
confidence: 99%